HASIL BELAJAR IPAS MENGGUNAKAN MODEL PEMBELAJARAN TGT BERBANTUAN MEDIA RODA PUTAR PADA SISWA KELAS IV SD N PATI WETAN 03 - Motik Dwi Isjayanti; Erik Aditia Ismaya; Khamdun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Class IV teacher learning activities at SD N Pati Wetan 03 are still using the teacher center learning method, which means teacher-centered learning. At the time of learning the lack of teachers in applying learning models and media as a support for achieving learning objectives. In accordance with these problems, the researcher was interested in examining whether there was an influence by applying the TGT learning model assisted by the rotary wheel media on the learning outcomes of class IV Science at SD N Pati Wetan 03. This research was a quantitative study using the one group pretest-posttest experimental method. The instrument used is a test instrument that aims to measure student learning outcomes with 10 multiple choice questions and 5 essay questions. The analysis technique used is the normality test and paired sample t-test. Based on the results of the normality test analysis, namely the pretest sig. 0.144 > 0.05 and posttest sig. 0.62 > 0.05, it can be seen that the data is normally distributed. In the paired sample t-test there is an analysis result with t count > t table (30.089 > 1.71714) and at significance that is 0.000 <0.05, it can be seen that there is a difference between the pretest and posttest results so it can be concluded that there is an influence by applying the learning model TGT assisted by rotating wheel media for science learning outcomes for fourth grade students at SD N Pati Wetan 03.